Algunas consideraciones y perspectivas sobre el test de razonabilidad: tras las huellas de las víctimas en el sistema de verdad, justicia y reparación de derechos (2011)
The purpose of this essay is to analyze the influence that the test of proportionality of fundamental rights has on the system of reincorporation of illegal groups in the Law 975 of 2005.Jurisprudence and other sources of law consulted will foster an analysis of the problem upon the joint support of instruments of criminal policy and constitutional law in order to rebuild the theory with which such rules are supported in Colombia. From an academic viewpoint, this will lead to tackle both the theory and criminal policy that have been applied as of today visàvis Law 975 of 2005 on matters of truth, justice and redress. Or what it will be: the approach of a justice that seeks redress vs. a justice that seeks restoration.